Long-range effect in ion-implanted polymers. (June 2022) - Kavetskyy, Taras; Stebeletska, Nataliia; Borc, Jaroslaw; Kravtsiv, Mariana; Graz, Katarzyna; Šauša, Ondrej; Švajdlenková, Helena; Kleinová, Angela; Kiv, Arnold; Tadeush, Olga; Stepanov, Andrey L.
Abstract: Long-range effect (LRE), which is known for ion-implanted crystals of diamond, metals and semiconductors, has also been observed in ion-implanted polymers. The effect is that a change in the physical characteristics of the material is observed far beyond the region of ion penetration into the sample. The present study was performed with polymethylmethacrylate (PMMA) implanted with 40 keV B + ions with different fluences of ions and current density less than 2 μA cm −2 . The samples were studied by nanoindentation technique with an ultra-nanohardness tester (UNHT), positron annihilation lifetime spectroscopy (PALS), and attenuated total reflection Fourier-transform infrared spectroscopy (ATR-FTIR). It was found that the changes of nanohardness induced by ion irradiation are observed up to a distance of about 1300 nm from the surface. This distance is much larger the size of implanted region that is of about 400 nm. The obtained PALS and ATR-FTIR results also testify that the microstructural changes occur far beyond the implanted layer of polymer. It is assumed that the observed effect is explained by the occurrence of internal mechanical stresses due to polymer carbonization in the implanted region of the sample. Highlights: Long-range effect (LRE) is found for ion-implanted polymers. The effect is that a change in the physical characteristics of the material is far beyond of ion penetration into the sample. The effect is confirmed by using independent methods – nanoindentation, positron annihilation and infrared spectroscopy. In all cases of ionic treatment of polymers, the LRE must be taken into account.